How China became capitalist - Coase, R. H. (Palgrave Macmillan, 2012)
"How China Became Capitalist details the extraordinary, and often accidental, journey that China has taken over the past thirty years in transforming itself from a closed agrarian socialist economy to an indomitable force in the international arena. The authors revitalize the debate around the development of the Chinese system through the use of primary sources. They persuasively argue that the reforms implemented by the Chinese leaders did not represent a concerted attempt to create a capitalist economy, but that the ideas from the West eventually culminated in a fundamental change to their socialist model, forming an accidental path to capitalism. Coase and Wang argue that the pragmatic approach of "seeking truth from fact" is in fact much more in line with Chinese culture. How China Became Capitalist challenges the received wisdom about the future of the Chinese economy, arguing that while China has enormous potential for growth, this could be hampered by the leaders' propensity for control, both in terms of economics and their monopoly of ideas and power"--